2007
DOI: 10.1007/s00264-007-0393-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the aetiology of adolescent idiopathic scoliosis

Abstract: The aetiology of adolescent idiopathic scoliosis (AIS) is still unknown despite many years of research effort. Theories on AIS's aetiology have included mechanical, hormonal, metabolic, neuromuscular, growth, and genetic abnormalities. Amongst these, some factors may be epiphenomena rather than the cause itself. Other factors may even contribute to curve progression, rather than curve initiation. Current views maintain that AIS is a multifactorial disease with genetic predisposing factors [Lowe et al. in J Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 57 publications
2
44
0
2
Order By: Relevance
“…Another prerequisite for the progression of adolescent idiopathic scoliosis is the presence of an adolescent growth spurt (Lowe et al, 2000;Cheung et al, 2008), but it is disputed whether Homo erectus already evolved this distinctive human growth pattern (Smith, 1993;Tardieu, 1998;Smith, 2004;Zihlman et al, 2004;Graves et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another prerequisite for the progression of adolescent idiopathic scoliosis is the presence of an adolescent growth spurt (Lowe et al, 2000;Cheung et al, 2008), but it is disputed whether Homo erectus already evolved this distinctive human growth pattern (Smith, 1993;Tardieu, 1998;Smith, 2004;Zihlman et al, 2004;Graves et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is now increasing evidence to support a role for abnormal spinal bone tissue as a primary intrinsic driver of AIS pathogenesis and a key determinant of curve progression [12,15]. It is has previously been reported that AIS patients exhibit lower lumbar spine bone mineral density (LSBMD) [9,10,55] and altered vertebral growth [9,10,29], resulting in disparity between the growth of anterior and posterior vertebrae, resulting in rotational lordosis.…”
Section: Intrinsic Factors Of the Ais Spinal Musculoskeletal System Smentioning
confidence: 99%
“…The consensus is therefore that AIS is a multifactorial disease [12], with increasing evidence from genetic studies for the central role of intrinsic factors in contributing to its pathology and progression. Ultimately, clarifying the molecular basis for these pathogenic drivers will facilitate the development of pharmacological therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the etiopathogeny is still unclear, largely due to its multifactorial origin (Weinstein et al, 2008). While a clear genetic basis is lacking so far (Miller, 2007), AIS is correlated in part with abnormal levels of tyrosine, sex and growth hormones, dysfunction of the melatonin-signaling pathway, and calcium-binding receptor protein calmodulin (Ahn et al, 2002;Moreau et al, 2004;Azeddine et al, 2007;Cheung et al, 2008). These biochemical abnormalities, however, might be more related to the progression rather than the origin of AIS (Kindsfater et al, 1994;Machida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%